THE EFFECT OF USING MEMRISE APPLICATION IN LEARNING ENGLISH VOCABULARY AT THE EIGHTH GRADE OF SMPN 4 BUKITTINGGI - Abdul Aziz; Veni Roza; Reflinda; Melyann Melani (STKIP Subang, 2026)
This research is driven by the crucial role of vocabulary mastery in English learning and the challenges encountered by junior high school students, including limited vocabulary knowledge, low learning motivation, and unvaried teaching techniques. These issues highlight the necessity for innovative learning media that can enhance students’ engagement and effectiveness in vocabulary acquisition. One alternative solution is the Memrise application, which integrates spaced repetition, multimedia features, and gamification to support vocabulary learning The objective of this study is to examine whether the use of the Memrise application significantly affects eighth-grade students’ English vocabulary learning at SMPN 4 Bukittinggi. This study applied a quantitative approach with a quasi-experimental research design. The population comprised all eighth-grade students of SMPN 4 Bukittinggi, from which two classes were selected as samples: an experimental group that received instruction using the Memrise application and a control group that was taught through conventional teaching methods. The data were gathered through vocabulary pre-tests and post-tests and analyzed using both descriptive and inferential statistics with the help of SPSS.